2011
DOI: 10.1007/978-3-642-24148-2_10
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of the Unified Theory of Acceptance and Use of Technology (UTAUT)

Abstract: Part 4: Customer and User IntegrationInternational audienceThe originating article of the Unified Theory of Acceptance and Use of Technology (UTAUT) has been cited by a large number of studies. However, a detailed examination of such citations revealed that only small proportion (43 articles) of these citations actually utilized the theory or its constructs in their empirical research for examining IS/IT related issues. In order to examine whether the theory is performing consistently well across various studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
133
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 214 publications
(182 citation statements)
references
References 39 publications
15
133
2
4
Order By: Relevance
“…The adjusted R 2 (Figure 2) falls within the average R 2 (0.30<R2<0.700.39) reported by Dwivedi et al (2011) and the R 2 (0.39) of the original UTAUT. Though PE was the main indicator in the original UTAUT, in the context of librarians' acceptance of RFID based LMS, PE is the least contributing indicator.…”
Section: Performance Of the Validated Adapted Modelsupporting
confidence: 77%
See 2 more Smart Citations
“…The adjusted R 2 (Figure 2) falls within the average R 2 (0.30<R2<0.700.39) reported by Dwivedi et al (2011) and the R 2 (0.39) of the original UTAUT. Though PE was the main indicator in the original UTAUT, in the context of librarians' acceptance of RFID based LMS, PE is the least contributing indicator.…”
Section: Performance Of the Validated Adapted Modelsupporting
confidence: 77%
“…A meta-analysis by Dwivedi et al (2011) identified several external variables used by other studies in adapted versions of UTAUT, among which are attitude, anxiety, self-efficacy, trust, perceived ease-of use, perceived usefulness, etc. that have significant, not significant or mixed influence on behavioural intentions.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although these values are not high, such explanation is acceptable in studies seeking to predict human behavior. Overall, the research findings provided support for the conclusion drawn by Dwivedi et al (2011) that UTAUT under-performs in different cultures and contexts. Third, the model constructs and their reliability and validity were supported, which further advocates the use of this framework in different cultural contexts.…”
Section: The Original Utautsupporting
confidence: 72%
“…According to (Williams et al, 2011;Dwivedi et al, 2011), gender as a moderating variable in UTAUT cited articles has not been considered along with all constructs of UTAUT model.…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%